2000
DOI: 10.3354/meps207069
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene glycosides defend the Caribbean reef sponge Erylus formosus from predatory fishes

Abstract: The reef sponge Erylus formosus (Demospongiae: Geodiidae) from the Bahamas and southern Florida contains a suite of triterpene glycosides that, at a natural volumetric concentration, deters predation by the fish Thalassoma bifasciatum in laboratory assays, and a natural assemblage of reef fishes in field assays. Antifeedant metabolites were isolated by bioassay-guided fractionation of extracts of E. formosus using standard chromatographic methods and identified by nuclear magnetic resonance (NMR) spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 38 publications
2
67
0
Order By: Relevance
“…264 In a subsequent study, cholesterol 66, 22-dehydrocholesterol 67, 22-dehydro-7)3-hydroxycholesterol 68, and 24-methylenecholesterol 69 were isolated as the active metabolites from Alcyonium paessleri while homarine 70 and trigonelline 71 were isolated as the active metabolites from Gersemia antarctica. 212 Ecologically relevant concentrations of these metabolites were found in the seawater surrounding the soft corals posing a potential barrier to predators. Extracts of the surrounding seawater also inhibited the growth of three sympatric microbes.…”
Section: Octocoralsmentioning
confidence: 99%
“…264 In a subsequent study, cholesterol 66, 22-dehydrocholesterol 67, 22-dehydro-7)3-hydroxycholesterol 68, and 24-methylenecholesterol 69 were isolated as the active metabolites from Alcyonium paessleri while homarine 70 and trigonelline 71 were isolated as the active metabolites from Gersemia antarctica. 212 Ecologically relevant concentrations of these metabolites were found in the seawater surrounding the soft corals posing a potential barrier to predators. Extracts of the surrounding seawater also inhibited the growth of three sympatric microbes.…”
Section: Octocoralsmentioning
confidence: 99%
“…As shown in Fig. 1F, using RT-PCR with primers designed to amplify a segment within the putative ORF of the functional clone, we also detected a transcript in RNA from heads of the bluehead wrasse (Thalassoma bifasciatum), a marine fish that co-occurs with the sponge E. formosus, a source of formoside (20). Comparison of the DNA sequence from the RT-PCR products from bluehead wrasse and the corresponding region of clone A9-f4-230 indicated 100% identity between these two divergent fishes (Fig.…”
mentioning
confidence: 99%
“…Furthermore, Xenopus oocytes expressing a zebrafish cDNA library, the cystic fibrosis transmembrane conductance regulator (CFTR), and the beta-2 adrenergic receptor (β 2 AR) exhibited a receptor-mediated electrophysiological response to formoside, a triterpene glycoside deterrent found in the sponge Erylus formosus (19,20). Using CFTR chloride channels to monitor activation of β 2 AR, we found that the kinetics of the formoside-mediated response in oocytes expressing the cDNA library suggest that the zebrafish genome encodes a protein whose activation by formoside causes a G protein-signaling cascade culminating in activation of CFTR.…”
mentioning
confidence: 99%
“…Since these contributions, saponins have been isolated from numerous species of Aspidochirotida and Dendrochirotida and also from sea stars (Mackie and Turner, 1970;Kitagawa and Kobayashi, 1977;Demeyer et al, 2014). More recently, they have also been noted in sponges (Thompson et al, 1985;Kubanek et al, 2000) and in chrysomelid beetles (Plasman et al, 2000a, b). Saponins have been reported to possess a wide range of biological activities including hemolytic, antitumoral, anti-inflammatory, antifungal, anti-bacterial, cytostatic, and ichthyotoxic properties (Kalinin et al, 1996a(Kalinin et al, , b, 2008Prokofeva et al, 2003;Bordbar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%